Antimicrobial and cytotoxic activity of (thio)alkyl hexopyranosides, nonionic glycolipid mimetics - Džubák, Petr; Gurská, Soňa; Bogdanová, Kateřina; Uhríková, Daniela; Kanjaková, Nina; Combet, Sophie; Klunda, Tomáš; Kolář, Milan; Hajdúch, Marian; Poláková, Monika (Carbohydrate research, 2020)
A series of 19 synthetic alkyl and thioalkyl glycosides derived from d-mannose, d-glucose and d-galactose and having C10-C16 aglycone were investigated for cytotoxic activity against 7 human cancer and 2 non-tumor cell lines as well as for antimicrobial potential on 12 bacterial and yeast strains. The most potent compounds were found to be tetradecyl and hexadecyl β-d-galactopyranosides (18, 19), which showed the best cytotoxicity and therapeutic index against CCRF-CEM cancer cell line. Similar cytotoxic activity showed hexadecyl α-d-mannopyranoside (5) but it also inhibited non-tumor cell lines. Because these two galactosides (18, 19) were inactive against all tested bacteria and yeast strains, they could be a target-specific for eukaryotic cells. On the other hand, β-D-glucopyranosides with tetradecyl (11) and hexadecyl (12) aglycone inhibited only Gram-positive bacterial strain Enterococcus faecalis. The studied glycosides induce changes in the lipid bilayer thickness and lateral phase separation at high concentration, as derived from SAXS experiments on POPC model membranes. In general, glucosides and galactosides exhibit more specific properties. Those with longer aglycone show high cytotoxicity and therefore, they are more promising candidates for cancer cell line targeted inhibition.
Keywords: glykosidy; proliferace buněk; Lipid Bilayers; Carbohydrate Sequence; buněčné linie; lipidové dvojvrstvy; mikrobiální testy citlivosti; Scattering, Small Angle; HCT116 buňky; Molecular Structure; lidé; HCT116 Cells; maloúhlový rozptyl; Antineoplastic Agents; protinádorové látky; Anti-Bacterial Agents; A549 Cells; Cell Line; molekulární struktura; Microbial Sensitivity Tests; sacharidové sekvence; X-Ray Diffraction; difrakce rentgenového záření; Glycosides; K562 Cells; galaktosa; Cell Proliferation; Galactose; Enterococcus faecalis; Cell Survival; viabilita buněk; antibakteriální látky; buňky K562; buňky A549; Humans